Histomorphological and Histochemical Studies on Esophagus in Gaddi Sheep (Ovis aries) - Malik, Shabir Ahmad; Rajput, Rajesh; Rafiq, Mohd; Faroque, Uiase bin; Gori, Haish Bhai (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present work was conducted to study the histoarchitecture and histochemical characteristics of esophagus in six adult Gaddi sheep. Lamina epithelialis consisted of keratinized stratified squamous epithelium with four functional regions: stratum corneum, stratum granulosum, stratum spinosum and stratum basale. In the stratum spinosum layer, the cell nuclei appeared polygonal whereas in the stratum corneum the cell nuclei were flattened and condensed. The stratum spinosum was the thicker layer and stratum granulosum was a thin layer that contained basophilic keratohyalin granules. Pyknotic cells were observed towards the luminal side of stratum corneum. Blood capillaries and lymphoid aggregations in the form of dark stained cells were present in the connective tissue of lamina propria. Connective tissue of lamina propria layer was denser than the same of the submucosa. The tunica muscularis consisted of striated muscle cells throughout the length of esophagus. Stratum corneum of the stratified epithelium of esophagus showed strong periodic acid-Schiff reaction indicating accumulation of glycogen whereas the cells of the basal layer lacked glycogen. The intercellular spaces in the upper layers of stratum spinosum of the epithelium contained acidic mucopolysaccharides as indicated by their reactivity to alcian blue stain.